PENGARUH LEADER MEMBER EXCHANGE, EMPOWERMENT DAN TALENT MANAGEMENT TERHADAP TURNOVER INTENTION KARYAWAN PT. SUBUR JAYA KOTA TENGAH - Erna; Makmur (Fakultas Ekonomi Universitas Pasir Pengaraian, 2018)
This study aims to determine the effect of leader member exchange, empowerment and talent management on employee turnover intentions of PT. Subur Jaya Kota Tengah both partially and simultaneously. The population in this study are all employees who work at PT. Subur Jaya Kota Tengah. The research sample used a purposive sampling technique, with a total of 59 people. Data collection methods using observations and questionnaires. Data analysis using multiple linear regression with the help of SPSS program. From the partial test results, the value of tcount leader member exchange is 14,951, tcount empowerment is 24,400 and tcount is talent management 9,915. The conclusion of this study is based on the results of partial testing and simultaneously testing leader member exchange, empowerment and talent management has a significant effect on employee turnover intention of PT. Subur Jaya Kota Tengah. The magnitude of the effect shown is 96.1%, while the rest is 3.9% turnover intention explained by other variables not examined in this study or other causes outside the model.